Need and Evolution of E-Learning In Presnt Era In India (International Journal of Innovative Research in Engineering & Management, 2021)
The higher education sector is in the midst of  fundamental change. Never before has there been such intense  public debate about the place of the university and its role in society.  During the 1980s and 1990 there was significant growth in the  number of student studying part–time and through distance  learning. The single most dramatic effect of paradigm shift is  learner sovereignty. The teacher role at least as defined by the  instructvists now belongs to a bygone era. Students have much  greater autonomy over their learning, in terms of when, where and  how they learn. Interaction with fellow students and faculty are  literally (and metaphorically) at their fingertips. In this review paper  an asynchronous discussion boards as the modus operandi, learner  interaction is heightened.
Keywords: Teaching; Educational Growth; E-learning; Formal and In-formal E-learning